Menguji efek pengungkapan CSR berbasis standar GRI 2021 terhadap kinerja keuangan perusahaan unggulan: Analisis empiris indeks LQ45 - Sania Revalina Budiman; Inggriani Elim; ⁠Sherly Pinatik (Yayasan Widyantara Nawasena Raharja, 2026)
Corporate Social Responsibility (CSR) serves as a strategic commitment toward stakeholders to ensure long-term corporate sustainability. This study investigates the impact of CSR disclosure on the financial performance of companies listed on the Indonesian LQ45 Index during the 2021–2024 period. Financial performance is proxied by Return on Assets (ROA), while CSR disclosure is measured using the Corporate Social Responsibility Disclosure Index (CSRDI) based on the latest Global Reporting Initiative (GRI) 2021 Standards. Utilizing a quantitative approach with purposive sampling, a total of 100 firm-year observations were analyzed through simple linear regression. The empirical results demonstrate that CSR disclosure has a positive but statistically insignificant effect on financial performance. This suggests that extensive sustainability reporting by market leaders has not yet been translated into immediate profitability improvements. These findings imply that market participants in the LQ45 index may perceive CSR compliance merely as a regulatory mandate rather than a short-term financial driver, highlighting the need for long-term evaluation of sustainability investments.